The Existence Of Tabaus Tradition As Traditional Channel In Buano Society, Maluku - Sukmawati, Lilis; Tuhuteru, Ajuan (DIALEKTIKA, 2023)
Tradition is a self-identity that must be maintained as a characteristic of an indigenous people, therefore certain efforts need to be made to preserve this tradition. This study aims to explore the supporting factors of Tabaus as a traditional communication channel in disseminating information. This study uses a qualitative descriptive research method. Data obtained through observation, interviews and documentation. As for the determination of informants carried out by purposive sampling technique.Furthermore, the research results obtained in this study indicate that the efforts of the people of North Buano State in maintaining Tabaus as a traditional communication channel in society for several reasons, namely the Tabaus Tradition is the result of the thoughts of predecessors who have an important role in the social life of society, Tabaus is a cultural heritage that is must be preserved, and the construction of community reality that builds confidence to maintain tradition because of the philosophy of life for the community when carrying out this tradition. Tabaus is not only a channel for conveying information, but as a key tradition for the continuation of information and social balancing for the people of the country which consists of 30 clans or families.